Efficacy of Curcumin on Inflammatory Biomarkers in Type 2 Diabetes: A Meta-Analysis of Clinical Trials and Animal Studies Systematic Review & Meta-Analysis (PRISMA 2020) Field: Botany & Complementary Medicine (Al-Farooq Journal of Sciences, 2026)
Background: Type 2 diabetes mellitus (T2DM) is among the most prevalent metabolic disorders worldwide, with the International Diabetes Federation estimating a global burden exceeding 537 million adults and projections pointing toward 783 million by 2045. Central to its pathogenesis is a state of chronic, low-grade inflammation driven by dysregulated cytokine release, persistent NF-κB activation, and adipokine imbalance. Curcumin, the principal polyphenolic constituent of Curcuma longa L. (Zingiberaceae), has attracted sustained scientific interest for its multi-target anti-inflammatory properties. Yet despite a growing body of trial-level evidence, no prior meta-analysis has concurrently integrated human randomized controlled trials (RCTs) and controlled animal experiments within a unified analytical framework.Objectives: To evaluate the pooled efficacy of curcumin supplementation on the three principal inflammatory biomarkers of T2DM—tumour necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), and C-reactive protein (CRP)—across human and animal studies, and to identify the formulation, dosage, and duration parameters most predictive of therapeutic response.Methods: A comprehensive literature search was conducted in PubMed/MEDLINE, Scopus, Web of Science, Cochrane CENTRAL, Embase, and Google Scholar. Study selection and data extraction adhered to PRISMA 2020 guidelines, with risk of bias assessed using Cochrane RoB 2.0 for RCTs and the SYRCLE tool for animal studies. Pooled effect sizes were expressed as weighted mean differences (WMD) or standardized mean differences (SMD) with 95% confidence intervals under a DerSimonian–Laird random-effects model.Results: Twenty-eight studies met the eligibility criteria—18 RCTs collectively enrolling 1,382 T2DM patients and 10 controlled animal experiments. Curcumin supplementation produced statistically significant reductions in CRP (SMD = −0.59, 95% CI: −1.11 to −0.07, p = 0.03), TNF-α (WMD = −1.84 pg/mL, 95% CI: −2.91 to −0.77, p = 0.001), and IL-6 (WMD = −1.29 pg/mL, 95% CI: −2.16 to −0.42, p = 0.004). Substantial heterogeneity was observed across all biomarkers (I² = 58–71%), with formulation type emerging as the dominant moderator.Conclusion: Curcumin exerts a consistent, mechanistically coherent anti-inflammatory effect in T2DM across both human and animal evidence. Enhanced-bioavailability formulations confer the largest benefits. These findings support curcumin's potential role as an adjunct anti-inflammatory strategy in T2DM management, pending confirmation by larger, standardized clinical trials.
Keywords: Curcumin; Type 2 Diabetes Mellitus; TNF-α; IL-6; CRP; NF-κB; Meta-Analysis; Systematic Review; Inflammation; Complementary Medicine; PRISMA 2020